Fast, selective and metal-free ring-opening polymerization to synthesize polycarbonate/polyester copolymers with high incorporation of ethylene carbonate using an organocatalytic phosphazene base. Issue 43 (23rd October 2019) - Wei, Chuanzhi; Kou, Xinhui; Liu, Shaofeng; Li, Zhibo
Abstract : Polycarbonate/polyester copolymers with high incorporation of EC were realized by a fast and selective process using a metal-free catalyst. Abstract : Ring-opening polymerization (ROP) is a powerful method used for converting cyclic monomers to polymers, but ethylene carbonate (EC), which has a five-membered ring, is an exception owing to the unfavorable thermodynamics of its ring-opening reaction unless the release of CO2 . This behavior stems from the faster cyclization to form a stable five-membered ring in comparison to the direct ring-opening reaction. Hence, many attempts have been made to copolymerize EC with other cyclic monomers such as cyclic esters to overcome the thermodynamic barrier. In this context, the copolymerization of EC with various cyclic esters, including ε-caprolactone (CL), δ-valerolactone (VL) and l -lactide (LLA), has been successfully achieved using an organocatalytic phosphazene superbase, such as a cyclic trimeric phosphazene base (CTPB ). The random copolymerizations proceeded fast with a turnover frequency (TOF) of 19 800 h −1 under mild polymerization conditions and afforded the corresponding copolymers without formation of the ether unit. Under all kinds of experimental conditions, no homopolymerization of EC occurred. The molecular structures of the obtained P(EC- co -CL) copolymers were characterized using 1 H NMR and 13 C NMR, which demonstrated that ca. 38 mol% EC can be incorporated within the copolymer chain depending on the different ratios of the EC and CL monomers. With the same catalytic system and under similar conditions, the amounts of EC incorporated into EC/VL (up to 26 mol%) and EC/LLA ( ca. 4.8 mol%) copolymerizations were lower than that for the EC/CL copolymerization. 2D NMR ( 1 H– 1 H correlated spectroscopy (COSY), 1 H– 13 C heteronuclear single quantum coherence (HSQC) and 1 H– 13 C heteronuclear multiple bond correlation (HMBC)) were performed to confirm the assignments in the 1 H NMR and 13 C NMR spectra of the copolymers and to better understand the chain structures of the copolymers. Therefore, polycarbonate/polyester copolymers with greater incorporation of EC were realized using a fast, selective and metal-free process.